A Self-Adaptive Extragradient Algorithm for Solving Quasimonotone Variational Inequalities - Li-Jun Zhu; Tzu-Chien Yin (Journal of Function Spaces)
This article aims to research iterative schemes for searching a solution of a quasimonotone variational inequality in a Hilbert space. For solving this quasimonotone variational inequality, we propose an iterative procedure which combines a self-adaptive rule and the extragradient algorithm. We demonstrate that the procedure weakly converges to the solution of the investigated quasimonotone variational inequality provided the considered operator satisfies several additional conditions.